Feasibility of farm stay scheme in Singapore. - Chen, Yizhou. (2008)
This paper aims to explore the feasibility of a farm stay scheme in Singapore. Views of 150 locals were gathered via street surveys and it is found that in general, the farms are not widely recognized by the respondents.